MENINGKATKAN DIMENSI KREATIVITAS PROFIL LULUSAN MURID MELALUI MODIFIKASI PERMAINAN BOLA TANGAN BERBASIS PROBLEM BASED LEARNING DALAM PEMBELAJARAN PJOK DI SMPN 8 BANJARBARU - Rangga Saputra; Arie Rakhman; Trinaldi Andika Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
With adapted handball games at SMPN 8 Banjarbaru, this study attempted to improve the creative component of students' graduation profiles using a Problem Bssed Learning-based PJOK course. The two cycles of CAR that were used in the study consisted of planning, taking action, observing, and reflection. Data was collected through questionnaires, documentation, and observation. The study revealed that the graduate profile's creative component improved throughout each cycle. During the pre-cycle phase, the proportion of students' creative ideas that were deemed adequate was 60%. In Cycle I, the